Distinct sites of phosphorothioate substitution interfere with folding and splicing of the Anabaena group I intron - Lupták, Andrej (Oxford University Press, 2004)
Although the active site of group I introns is phylogenetically conserved, subclasses of introns have evolved different mechanisms of stabilizing the catalytic core. Large introns contain weakly conserved ‘peripheral’ domains that buttress the core through predicted interhelical contacts, while smaller introns use loop–helix interactions for stability. In all cases, specific and non-specific magnesium ion binding accompanies folding into the active structure. Whether similar RNA–RNA and RNA–magnesium ion contacts play related functional roles in different introns is not clear, particularly since it can be difficult to distinguish interactions directly involved in catalysis from those important for RNA folding. Using phosphorothioate interference with RNA activity and structure in the small (249 nt) group I intron from Anabaena, we used two independent assays to detect backbone phosphates important for catalysis and those involved in intron folding. Comparison of the interference sites identified in each assay shows that positions affecting catalysis cluster primarily in the conserved core of the intron, consistent with conservation of functionally important phosphates, many of which are magnesium ion binding sites, in diverse group I introns, including those from Azoarcus and Tetrahymena. However, unique sites of folding interference located outside the catalytic core imply that different group I introns, even within the same subclass, use distinct sets of tertiary interactions to stabilize the structure of the catalytic core.